Умови виховання моральної поведінки у дітей передшкільного віку засобами народної педагогіки - Рябоконь, Лариса Михайлівна (My University, 2023)
Робота присвячена розкриттю теоретичних і практичних засад такої важливої проблеми сьогодення, як моральне виховання дітей дошкільного віку. Автором взято до наукового аналізу віковий період 6-7 років, який є періодом підготовки вступу дитини до навчання у школі – передшкільним віком. Важливим засобом виховання визначається народна педагогіка. Упродовж віків народна виховна система накопичила багатий ресурс щодо формування у дітей явлень моралі, моральної поведінки. Автором досліджено проблему на теоретичному та емпіричному рівнях. Розроблено критерії та показники вихованості моральної поведінки передшкільного віку; на основі експериментального вивчення стану практики закладу дошкільної освіти визначено три рівні її сформованості. Виявлено чинники впливу на ефективність роботи з виховання в дітей моральної поведінки у ЗДО з урахуванням етнопедагогічної складової. Запропоновано програму експериментальної роботи щодо використання засад народної педагогіки у вихованні моральної поведінки дітей передшкільного віку.
Ryabokon L.M. Pedagogical conditions for the education of moral behavior in children of preschool age by means of folk pedagogy. - Qualification work. - Nizhin, 2023. – 93 p. The work is devoted to revealing the theoretical and practical foundations of such an important problem today as the moral education of preschool children. The author took into scientific analysis the age period of 6-7 years, which is the period of preparation for a child's entry into school - preschool age. Folk pedagogy is defined as an important means of education. Over the centuries, the national educational system has accumulated a rich resource for the formation of moral phenomena and moral behavior in children. The author investigated the problem at the theoretical and empirical levels. Criteria and indicators of upbringing of moral behavior of preschool age have been developed; based on an experimental study of the state of practice of the preschool education institution, three levels of its formation were determined. Factors influencing the effectiveness of the work on raising children's moral behavior in the ZDO, taking into account the ethno- pedagogical component, were identified. A program of experimental work on the use of the principles of folk pedagogy in the education of moral behavior of preschool children is proposed. Key words: morality, moral education, behavior, moral behavior, education of moral behavior, folk pedagogy, ethnopedagogy, preschool age, preschool age child.
Keywords: мораль; моральне виховання; поведінка; моральна поведінка; виховання моральної поведінки; народна педагогіка; етнопедагогіка; передшкільний вік